Oral potentially malignant disorder awareness level among elder community in the Belawa Distric, Wajo, South Sulawesi, Indonesia - Erni Marlina; Sumintarti; Harlina Ilmar; Ali Yusran; Nur A. Usman; Israyani; Andi A. Mauliana (DiscoverSys Inc., 2022)
Objective: to assess awareness of senior community in the Belawa distric, Wajo, South Sulawesi, Indonesia regarding their oral soft tissue abnormality specifically regard to Oral potentially malignant disorders, and to assess community ability to descript any pain or uncomfortably origin from their oral cavity. Methods: A self-made questionnaire written in Indonesia language was given to the old aged-adult based on WHO criteria with age range between 45 to 75 years old, who was willing to participate in this study. The questioner consists some picture representing oral mucosal cavity with clinical feature of some ulcers, clinical feature of candida infection, and some clinical appearances of oral potentially malignant disorders. Results: In term of oral mucosal diseases questions, 22 (55%) participants had history of ulceration, however only 5 (45%) participants could specifically point out its previous ulcer location. However, history of pain only stated by 11 (28%) participants, 24 (60%) did not experienced any pain, and 5 (12%) did not answer the questions. Conclusion: knowledge and awareness regarding oral health lesion, especially the associated-potentially malignant lesion was far from ideal in the Belawa Community.